EFFECT OF SHOCKS OF AGRICULTURAL TERMS OF TRADE (TOT) ON SOME AGRICULTURAL INDICATORS IN IRAQ FOR THE PERIOD (1990 - 2019) - AlAttabi, H. A.; B. H. AlBadri (The Iraqi Journal of Agricultural science)
This study aimed to investigate the impact of agricultural TOT shocks and the strength of their effects on some indicators of the agricultural sector. The research uses VAR, Variance decomposition and IRF approaches. The research is due to the almost monolithic exports and the multiplicity of imports, and the results of the agricultural product response to the shock of the agricultural gross terms of trade (GBTT) indicated that it had a negative impact, due to the shocks that the last variable was subjected to, which was reflected on an agricultural product, but they are not permanent as they returned to the normal situation within the sixth year. The research recommended adopting the TOT criterion as one of the criteria for drawing agricultural development plans in Iraq and one of its basic indicators to link the import capacity with the export capacity, as well as the need to pay attention to reviving agricultural exports to Iraq to stimulate agricultural terms of trade and then agricultural investment.